The Spectrum and Fine Spectrum of q-Cesàro Matrices with 0 < q < 1 on c0. (17th February 2020) - Yildirim, Merve Esra
Abstract: One of the q-analogs of the Cesáro matrix of order one is the triangular matrix with nonzero entries c nk = q n − k 1 + q + ⋯ + q n 0 ≤ k ≤ n, where q ∈ [ 0, 1 ] . In this paper, we determine the spectrum and various spectral separations of the spectrum of C 1 ( q ) = ( a nk ( q ) ) which is q -analog of the Cesáro matrix regarded as a bounded linear operator on the sequence space c 0 .